Maravilla: a variety of forage barley for High Valleys of Mexico - Zamora Díaz, Mauro; Pérez Ruiz, Juan Armando; Huerta Zurita, Ramón; López Cano, Martha Laura; Gómez Mercado, René; Rojas Martínez, Israel (Revista Mexicana de Ciencias Agrícolas, 2017)
Maravilla is a variety of forage barley obtained from a multiple crossbreeding conducted by the National Barley Program of the Instituto Nacional de Investigaciones Forestales, Agrícolas y Pecuarias. Maravilla shows a habit of spring growth, intermediate size, tolerance to the main diseases of the crop, has high potential yield and its precocity allows it to adapt to the weather conditions of High Valleys of the Mesa Central of Mexico. The chemical characteristics of the Maravilla grain represent an important nutrient supply: the concentration of crude protein varies from 10 to 14.5%; the starch concentration ranges from 61 to 66%; the average mineral content is 3.5%; the crude fiber average 3.5%; the average ethereal extract is 1.83%; the average nitrogen free extract is 74%, and the average dry matter digestibility is 95%. With respect to green forage, the optimum cutting time is when the grain is in the soft dough stage, where the yield is higher than 20 t ha-1; while in dry matter it is 8-12 t ha-1. Maravilla was evaluated in more than 30 experimental sites in different environments of the barley producing regions of Valles Altos during the period from 2012 to 2015. The grain yield observed was 2.1-5.2 t ha-1; similar and sometimes 5% superior to that of the malted barley Esmeralda variety.